2020
DOI: 10.1186/s12886-020-01527-5
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography (OCTA) findings in Serpiginous Choroiditis

Abstract: Background: To describe changes in the retina/choroid in patients with Serpiginous Choroiditis (SC) by Optical Coherence Tomography Angiography (OCTA) in a multimodal imaging approach. Methods: Prospective, monocentric study of 24 eyes of 12 consenting patients diagnosed with SC, who underwent OCTA, which was analyzed and compared to other methods such as enhanced depth imaging-OCT, fluorescein angiography, indocyanine green angiography, and fundus autofluorescence. Results: The study group consisted of 9 pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Macedo et al further demonstrated loss of inner retinal layers in more advanced stages of atrophy in SC, resulting in increased visibility of the choroid, which was isoreflective. In their study, OCTA imaging showed hypo-perfused choriocapillaris in all 12 patients with SC, which compared well with the atrophic areas found on EDI-OCT [24].…”
Section: Image Of Serpiginous Choroiditis In Swept-source Optical Coh...supporting
confidence: 54%
See 1 more Smart Citation
“…Macedo et al further demonstrated loss of inner retinal layers in more advanced stages of atrophy in SC, resulting in increased visibility of the choroid, which was isoreflective. In their study, OCTA imaging showed hypo-perfused choriocapillaris in all 12 patients with SC, which compared well with the atrophic areas found on EDI-OCT [24].…”
Section: Image Of Serpiginous Choroiditis In Swept-source Optical Coh...supporting
confidence: 54%
“…Although SC is a rare disease, the authors working on this issue have demonstrated the reliability of a technique such as OCTA in the diagnosis of SC over existing diagnostic methods (ICGA, FA, FAF) [7,24].…”
Section: Image Of Serpiginous Choroiditis In Swept-source Optical Coh...mentioning
confidence: 99%
“…This cross-sectional study enrolled patients with BSRC and SC who were scheduled for an examination with multimodal imaging technique at Charité University of Medicine Berlin [21,22]. Each patient was informed about the study and has given written consent.…”
Section: Patient Recruitmentmentioning
confidence: 99%